2019
DOI: 10.1002/ece3.5010
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities within Phengaris (Maculinea) alcon caterpillars are shifted following transition from solitary living to social parasitism of Myrmica ant colonies

Abstract: Bacterial symbionts are known to facilitate a wide range of physiological processes and ecological interactions for their hosts. In spite of this, caterpillars with highly diverse life histories appear to lack resident microbiota. Gut physiology, endogenous digestive enzymes, and limited social interactions may contribute to this pattern, but the consequences of shifts in social activity and diet on caterpillar microbiota are largely unknown. Phengaris alcon caterpillars undergo particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 87 publications
1
6
0
Order By: Relevance
“…We found that all tested bacterial communities were predominated by three phyla (Proteobacteria, Actinobacteria, and Firmicutes), with each comprising a different share of the microbiome depending on species or sample tested (Table S1). Those phyla are frequently listed as the most abundant in bacterial communities associated with insect taxa [61][62][63][64], including ants [49,[65][66][67][68][69][70] and myrmecophilous caterpillars of Lycaenidae butterflies [71][72][73]. In some cases, the joint abundance of those phyla may exceed even 90% of bacterial community membership [63].…”
Section: Discussionmentioning
confidence: 99%
“…We found that all tested bacterial communities were predominated by three phyla (Proteobacteria, Actinobacteria, and Firmicutes), with each comprising a different share of the microbiome depending on species or sample tested (Table S1). Those phyla are frequently listed as the most abundant in bacterial communities associated with insect taxa [61][62][63][64], including ants [49,[65][66][67][68][69][70] and myrmecophilous caterpillars of Lycaenidae butterflies [71][72][73]. In some cases, the joint abundance of those phyla may exceed even 90% of bacterial community membership [63].…”
Section: Discussionmentioning
confidence: 99%
“…Symbiotic bacteria play a pivotal role in the development and survival of their insect hosts, providing a full array of molecules for digestion, detoxification, and defense against pathogens (Douglas, 2015). There is still a scant knowledge on Lepidoptera-associated microbiomes, because the majority of studies is (i) merely descriptive, (ii) focused on single bacterial taxon, (iii) a few butterfly/moth species have been extensively surveyed, or (iv) only rarely endosymbionts have been compared across different developmental instars (Di Salvo et al, 2019;Gao et al, 2019;Szenteczki et al, 2019). Nevertheless, an increasing number of experiments provide evidence for a crucial function of microbes in basic physiological processes of Lepidoptera (Paniagua Voirol et al, 2018), e.g.…”
Section: A Third Player: Egg-associated Microorganismsmentioning
confidence: 99%
“…In turn, Fischer et al (2017) have shown that bacteria may contribute to the recognition of distant aphid species by Lasius niger ants (Fischer et al 2017). These results strengthen interest in studying the role of microorganisms in shaping relationships among closely associated species (Szenteczki et al 2019;Kaczmarczyk-Ziemba et al 2020).…”
Section: Introductionmentioning
confidence: 64%
“…The microbiota of Lasius fuliginosus and Pella laticollis 2019; Szenteczki et al 2019;Kaczmarczyk-Ziemba et al 2020)). In the present study, we have extended the state of the art regarding the microbiota of ants and their associates by investigating the potential similarities among the bacterial communities associated with two closely interacting species, L. fuliginosus and P. laticollis (both larvae and adults).…”
Section: Resultsmentioning
confidence: 99%